PROCLAMATION OF PATRIARCH OF SREMSKI KARLOVCI PROKOPIJE IVACKOVIC - Дејан Микавица; Горан Васин (Истраживања, 2011)
After Patriarch Samuilo Masirevic had died in January of 1870, there were several attempts on several occasions to reelect new first bishop of The Metropolitanate of Karlovci. On church-national assemblies held in 1871 and 1872 the majority of Liberal Party representatives supported Arsenije Stojkovic, bishop from Buda. However, the government in Budapest disagreed with such election. Similar thing happened with bishop of Pakrac well known Nikanor Grujic. That is how bishop Stojkovic got reelected on church-national assembly which was held in June/July of 1874 in Sremski Karlovci. Still, the government refused to acknowledge the election will of its representatives forcing the election of Prokopije Ivackovic metropolitan of Romanian church. Soon this election was officially confirmed in accordance with the law of dual monarchy by the ruler himself thus marking the beginning of new metropolitan-patriarch rule over Metropolitanate which had lasted until 1879.